Cover Feature: Rationalizing Photo‐Triggered Hydrogen Evolution Using Polypyridine Cobalt Complexes: Substituent Effects on Hexadentate Chelating Ligands (ChemSusChem 8/2021). Issue 8 (6th April 2021) - Lucarini, Fiorella; Bongni, David; Schiel, Philippe; Bevini, Gabriele; Benazzi, Elisabetta; Solari, Euro; Fadaei‐Tirani, Farzaneh; Scopelliti, Rosario; Marazzi, Marco; Natali, Mirco; Pastore, Mariachiara; Ruggi, Albert
Abstract : The Cover Feature shows the structure–activity relationship of a family of heptacoordinate Co II complexes for light‐triggered H2 evolution. The complexes present a ligand scaffold including bipyridines and pyridines moieties functionalized with either electron‐donating or electron‐withdrawing groups. Results show that position plays a predominant role with respect to the electronic effect of the substituents. More information can be found in the Full Paper by F. Lucarini et al .